2009
DOI: 10.1510/icvts.2008.201038
|View full text |Cite
|
Sign up to set email alerts
|

Mini re-sternotomy for aortic valve replacement in patients with patent coronary bypass grafts

Abstract: As the population ages, an increasing number of patients with patent coronary grafts will require subsequent aortic valve replacement. Major operative problems include those associated with re-entry and, in particular, damage of the patent grafts. Between January 2007 and October 2008, 10 patients who had previous coronary bypass surgery underwent aortic valve replacement through upper j-shaped mini re-sternotomy. In all patients the previous grafts were patent. The operation was performed with normothermic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…In this series, there were no CABG graft injuries and the 5-year actuarial survival was 85%. A small series of ten patients with previous CABG undergoing mini-AVR was also reported by Dell'Amore et al (36). There was no in hospital mortality and no injury to the bypass grafts.…”
Section: Re-do Minimally Invasive Aortic Valve Surgerysupporting
confidence: 62%
“…In this series, there were no CABG graft injuries and the 5-year actuarial survival was 85%. A small series of ten patients with previous CABG undergoing mini-AVR was also reported by Dell'Amore et al (36). There was no in hospital mortality and no injury to the bypass grafts.…”
Section: Re-do Minimally Invasive Aortic Valve Surgerysupporting
confidence: 62%
“…With a perioperative mortality of 2.3% ( = 1) for ministernotomy and 3.3% ( = 10) for sternotomy ( = 1.0), ministernotomy was not associated with higher perioperative mortality in our series. Our perioperative mortality was comparable to that in the current literature [1,3,[9][10][11][12]. The long-term survival in our series was slightly better following ministernotomy; the 1-, 3-and 7-year survival for ministernotomy was 93.8%, 93.2%, and 88.3%, respectively; for sternotomy, it was 87.7%, 83.7%, and 82.6%, respectively (95% CI 0.273 to 1.325, = .20); however, this difference in survival did not reach a level of statistical significance.…”
Section: Discussionsupporting
confidence: 83%
“…Other advantages include cosmetic benefits such as a smaller incision and keeping the sternum intact in the lower half of the chest [1]. Although some authors have recommended the ministernotomy for AVR [2,3], others have reported no advantage of minimally invasive AVR in early or midterm followup [4,5]. This study was undertaken to compare the outcomes of ministernotomy with those of conventional sternotomy.…”
Section: Introductionmentioning
confidence: 99%
“…4,5) The indication for surgery, initially restricted only to selected elective patients, is now extended to more complex surgeries, including both the aortic root, the ascending aorta and redo-operations. [4][5][6][7][8][9][10][11][12] Especially in complex aortic surgery and in high risk patients, a ministernotomy approach can improve respiratory function recovery and allow earlier extubation, reducing ICU and hospital stay. 6) Other authors have previously reported on surgery of the aortic root or ascending aorta through a ministernotomy.…”
Section: Discussionmentioning
confidence: 99%